Sequência didática: a importância dos conhecimentos prévios para a aprendizagem de termologia no sétimo ano - SILVA, Antônio Marcos Alves da (2022)
The present study, called TEACHING SEQUENCE: THE IMPORTANCE OF PRIOR KNOWLEDGE FOR LEARNING TERMOLOGY IN THE SEVENTH YEAR, linked to the National Professional Master's Degree in Physics Education (MNPEF) of the UFMA Graduate Program had as its main objective to elaborate a sequence didactics whose focus is to enable a pedagogical strategy to be applied in the teaching of Thermology contents, thus contributing to the teacher's work in the classroom and, consequently, to the improvement of learning. This study was concerned with analyzing the relevance of studying the discipline of science in elementary education and its importance in the formation of each student as a student and citizen; the concept of learning based on the works of some authors, including David Ausubel and his theory of meaningful learning; the role that the teacher plays in this scenario; the relevance of technological resources for teaching work; the contents studied in the final years of elementary school, especially the 7th year, in addition to the main concepts of termology, covered in this stage of school education. From a methodological point of view, firstly, a field research consisting of two questionnaires and a bibliographic one was used. From the systematization and analysis of the data, the educational product was elaborated TEACHING SEQUENCE: THE IMPORTANCE OF PREVIOUS KNOWLEDGE FOR LEARNING TERMOLOGY IN THE SEVENTH YEAR, which consists of the study of previous knowledge of the contents of termology with a view to its application in classrooms by professors who teach subjects in the science discipline. This effort was intended to contribute to the work of teachers. The results point to an improvement in learning by the students who participated in the application of the educational product, among which are better performance in proposed activities, in addition to explanations of phenomena present in daily life, as observed in the results of activities carried out during the educational product evaluation phase.